Delineation of cross-domain associations between everyday executive function and adaptive behaviour in Down syndrome and Williams syndrome - Darren R. Hocking; Elysse Byer; Nancy Raitano Lee (Scientific Reports, 2024)
Abstract In genetic syndromes such as Down syndrome (DS) and Williams syndrome (WS), difficulties with executive functioning (EF) are a commonly reported feature and a key correlate of long-term success in everyday life. Despite a robust literature in children with these syndromes, it remains unclear how cross-syndrome characteristics of everyday EF relate to adaptive functioning and intelligence among adults with DS and WS, and if these relationships differ between these groups. This study aimed to characterise the profile of strengths and weaknesses in everyday EF using the Behaviour Rating Inventory of Executive Function-Adult Informant Version (BRIEF-A) in older adolescents and young adults with DS and WS. Associations between distinct EFs, adaptive/maladaptive functioning, and intellectual ability were also investigated. Results showed that the WS group displayed profound impairments in almost all BRIEF-A scales, with a large percentage of scores in the clinically significant range. Further, selective EFs (Inhibit, Organisation of Materials, Task Monitor) were able to discriminate between the two genetic syndromes. Contrary to previous research, in WS, Working Memory was linked to adaptive functioning and IQ. In DS, the Task-Monitor and Shift scales were unique predictors of externalising and internalising behaviours, respectively. These findings could have important implications for targeted cognitive interventions in these genetic syndromes.